Foot and mouth disease in the Lao People's Democratic Republic: I. A review of recent outbreaks and lessons from control programmes. - Khounsy, S; Conlan, J; Gleeson, L; Westbury, H; Colling, A; Paton, D; Knowles, N; Ferris, N; Blacksell, S (2008)
Foot and mouth disease (FMD) causes sporadic disease outbreaks in the Lao People's Democratic Republic (Lao PDR). As the Lao PDR is a major thoroughfare for transboundary animal movements, regular FMD outbreaks occur, causing economic hardship for farmers and their families. In this review of the recent history of FMD in the Lao PDR between 1997 and 2006, the authors examine the virological and epidemiological aspects of the disease and appropriate control measures, including the distribution of outbreaks, causative serotypes and the molecular epidemiology of the viruses, as well as large-scale vaccination programmes. The dominant serotype, type O, was reported every year from 1998 to 2005. The majority of outbreaks occurred in Vientiane Capital (n = 42; 28%) and the highest number of outbreaks were reported in cattle (n = 94; 61%); followed by buffalo (n = 41; 27%) and pigs (n = 18; 12%). All type A outbreaks occurred in cattle. Type Asia 1 outbreaks were reported in the central provinces around Vientiane Capital between 1996 and 1998.